Cyclosporin A and tacrolimus reduce T-cell polyfunctionality but not interferon-γ responses directed at cytomegalovirus - Fuhrmann, Stephan (Blackwell Science Inc, 2012)
Cytomegalovirus (CMV) -specific immunity is often estimated by the number of in vitro CMV antigen-inducible interferon-γ-positive (IFN-γ(+)) T cells. However, recent work indicates that simultaneous production of IFN-γ, tumour necrosis factor-α (TNF-α) and interleukin-2 (IL-2) (referred to as ‘polyfunctionality’) is more relevant for anti-viral protection. Here, we compared polyfunctionality of CMV-specific T cells (pp65 and IE-1 proteins) in 23 solid-organ transplant patients and seven healthy controls by flow cytometry. The proportions of TNF-α(+)/IFN-γ(+)/IL-2 cells among the activated cells were significantly reduced in transplant patients but not the frequencies of IFN-γ(+) CD8(+) T cells. Immunosuppression reduces polyfunctionality, which reflects the increased infection risk in this patient group.